Dermoscopic features and follow‐up changes of acral melanocytic naevi in childhood and adolescence. (February 2014) - Fargnoli, M.C.; Suppa, M.; Micantonio, T.; Antonini, A.; Tambone, S.; Peris, K.
Summary Background The dermoscopic features of acral acquired melanocytic naevi have been extensively reported in the adult population. Little knowledge is available on acral naevi in childhood and adolescence. Objectives Firstly, to characterize the frequency of dermoscopic features of acral naevi and their distribution according to age groups in children and adolescents; and secondly, to analyse the type and frequency of their dermoscopic changes over time. Methods A retrospective evaluation of baseline and follow‐up dermoscopic images of acral naevi in Italian patients aged 0–18 years was carried out. Results Dermoscopic images of 75 acral naevi (39 in children and 36 in adolescents) in 69 patients were evaluated. The parallel furrow was the most common pattern (71%), followed by the crista dotted pattern (21%). A difference in the distribution of global patterns was observed between children and adolescents (P = 0·02). Combination patterns were detected in 32% of lesions, with association of the crista dotted and parallel furrow patterns in 62% of these. Follow‐up images were available for 31/75 acral naevi (41%), with a median follow‐up period of 32 months (range 4–85). Morphological variations during follow‐up were identified in 61% of lesions. Global changes involved mainly naevi with a baseline parallel furrow pattern, after a follow‐up of > 30 months. A decrease of local criteria during follow‐up was observed in 48% of lesions. Conclusions Parallel furrow and crista dotted patterns, either alone or in combination, were the most common dermoscopic patterns. Morphological changes during follow‐up were frequent, involving mainly the parallel furrow pattern with a decrease of local criteria. Recognition of the dermoscopic features of acral naevi of children and adolescents is important to improve proper management and reduce the number of unnecessary excisions.